The Implementation of the Notary Code of Conduct in Realizing Quality Notary Services - Jauhari, Rofiq (Jurnal Konstatering, 2022)
Notary is a public official who is authorized in making authentic deeds. As an official appointed by the government, a notary has the duty to provide good service to the community. In the duties of a Notary, it is regulated by several laws and regulations, especially the Law on Notary Positions and the Notary Code of Ethics. The method used in the preparation of this thesis is a sociological juridical method, namely research conducted by observation, collecting data from both the literature and interviews. The results of the study stated that 1) The implementation of the Notary Code of Ethics in realizing the quality of quality Notary services in the City of Rembang is as a basis, benchmark, reference and guideline / benchmark in every act, attitude and behavior in the duties of a notary position. The provisions contained in the notary code of ethics contain obligations and prohibitions for notary positions to regulate so that notaries do not violate mutually agreed rules. 2) Barriers & solutions to the implementation of the Notary Code of Ethics in realizing quality Notary services in the City of Rembang is the less than optimal role of Notaries, Regional Honorary Councils and the Community in Rembang City in realizing quality Notary services. The solution to the three obstacle factors is to work together in carrying out the roles of each individual/group in accordance with the applicable law so as to realize quality Notary services in the City of Rembang. solutions to the implementation of the Notary Code of Ethics in realizing the quality of Notary services in the City of Rembang is the less than optimal role of Notaries, Regional Honorary Councils and the Community in Rembang City in realizing the quality of Notary services. The solution to the three obstacle factors is to work together in carrying out the roles of each individual/group in accordance with the applicable law so as to realize quality Notary services in the City of Rembang. solutions to the implementation of the Notary Code of Ethics in realizing the quality of Notary services in the City of Rembang is the less than optimal role of Notaries, Regional Honorary Councils and the Community in Rembang City in realizing the quality of Notary services. The solution to the three obstacle factors is to work together in carrying out the roles of each individual/group in accordance with the applicable law so as to realize quality Notary services in the City of Rembang.Keywords: Code; Ethics; Notary.